Equilibrium Block Trading and Asymmetric Information. - Seppi, Duane J (Journal of Finance, 1990)
This paper investigates the existence of equilibria with information-based black trading in a multiperiod market when no investor is constrained to block trade. Attention is restricted to equilibria in which a strategic uninformed institution (i.e., one which is forced to rebalance its portfolio, but is free to choose an optimal rebalancing strategy) is willing to trade a block rather than "break up" the block into a series of smaller trades. Examples of such equilibria are found and analyzed.